Microscopic Seepage Mechanism of Gas and Water in Ultra-Deep Fractured Sandstone Gas Reservoirs of Low Porosity: A Case Study of Keshen Gas Field in Kuqa Depression of Tarim Basin, China - Wang, Rujun; Zhang, Chengze; Chen, Dong; Yang, Fenglai; Li, Haiming; Li, Ming (Frontiers in Earth Science, 2022)
To study the microscopic seepage mechanism of gas and water in fractured sandstones gas reservoirs of low porosity, this kind of reservoirs in Keshen Gas Field, Kuqa Depression of Tarim Basin in China was taken as an example. Based on rock samples and microscopic visualization technology, NMR experiments of saturated water-gas drive and CT scanning experiments of saturated gas-water drive were conducted. The seepage mechanism of water invasion during the gas development were simulated. Subsequently, the distribution of irreducible water saturation and the influence factors on efficiency of drive were analyzed. Results show that distribution of gas and water is mainly related to structures of matrix pores, fracture development pattern and density. Main factors resulting into good reservoirs include large matrix pores and high angle fractures, low irreducible water saturation and high separation between gas and water. The efficiency of water drive is positively correlated with fracture porosity and dip angle. High angle fractures can effectively improve the seepage capability, and then increase the efficiency of water drive. Besides, a great the proportion of large pore size in matrix, high fracture dip, porosity and density can also improve the efficiency of water drive. Therefore, for the development of fractured sandstones gas reservoirs of low porosity, the study of matrix pores and fractures is quite important since it can provide guidance for the efficient deployment of wells. The increase of fracture density is significant by large-scale sand fracturing, in order to improve the efficiency of water drive. It is necessary to strictly control the gas production rate of the gas reservoir and delay the water invasion rate as far as possible. In case of serious waterlogging, shut-in all wells in gas reservoirs is a choice to strengthen the gas-water imbibition between fractures and matrix, which can improve the recovery of the gas reservoir.